Migrasi dan Mobilisasi: Upaya Masyarakat Sumenep Madura Menjaga Marwah Keluarga (LPTNU Sumenep, 2023)
The burden of financially heavy household due to the emergence of new traditions that are constructed in the local community and because of the desire to preserve household prestige is the main issue raised in this article. The driving factors for mobilization and how to preserve household prestige through migration are two questions to be addressed. By using a qualitative approach to the phenomenon of migration and mobilization by a group of people in the Madurese Sumenep, data were obtained through observation, interviews and documents and analyzed descriptively-critically. This article finds two important things, namely, firstly, migration mobility occurs due to economic factors that squeeze the local society where the available jobs are not sufficient to meet the needs of their household. Moreover, they must cultivate agricultural land by cultivating crops that have become a family legacy. Second, migration mobility is driven by the desire to preserve the prestige or dignity of the household in order to equal in the eyes of the society and are not ostracized due to debt problems or not participating in the new traditions constructed by the local society.